The glycolytic shift was involved in CdTe/ZnS quantum dots inducing microglial activation mediated through the mTOR signaling pathway. Issue 3 (4th December 2019) - Wu, Tianshu; He, Keyu; Liang, Xue; Wei, Tingting; Wang, Yan; Zou, Lingyue; Zhang, Ting; Xue, Yuying; Tang, Meng
Abstract: The excellent optical property and relatively low toxicity of CdTe/ZnS core/shell quantum dots (QDs) make them an advanced fluorescent probe in the application of biomedicines, particularly in neuroscience. Thus, it is important to evaluate the biosafety of CdTe/ZnS QDs on the central nervous system (CNS). Our previous studies have suggested that the high possibility of CdTe/ZnS QDs being transported into the brain across the blood‐brain barrier resulted in microglial activation and a shift of glycometabolism, but their underlying mechanism remains unclear. In this study, when mice were injected intravenously with CdTe/ZnS QDs through tail veins, the microglial activation, polarized into both M1 phenotype and M2 phenotype, and the neuronal impairment were observed in the hippocampus. Meanwhile, the increased pro‐ and anti‐inflammatory cytokines released from BV2 microglial cells treated with CdTe/ZnS QDs also indicated that QD exposure was capable of inducing microglial activation in vitro. We further demonstrated that the glycolytic shift from oxidative phosphorylation switching into aerobic glycolysis was required in the microglial activation into M1 phenotype induced by CdTe/ZnS QD treatment, which was mediated through the mTOR signaling pathway. The findings, taken together, provide a mechanistic insight regarding the CdTe/ZnS QDs inducing microglial activation and the role of the glycolytic shift in it. Abstract : CdTe/ZnS quantum dot (QD) exposure through intravenous injection caused microglial activation after neuronal impairment in the hippocampus of mice. The increased pro‐ and anti‐inflammatory cytokines released from BV2 microglial cells treated with CdTe/ZnS QDs also indicated the microglial activation induced by QDs in vitro. The glycolytic shift from oxidative phosphorylation switching into aerobic glycolysis was required in the microglial activation induced by CdTe/ZnS QD treatment via the mTOR signaling pathway.